(untitled) (International Journal of Engineering and Computer Science, 2015)
-With rapid development of high-quality cameras and powerful photo-editing tools significantly reduces the difficulty to make visually plausible fake images. The JPEG format is widely used as one of the most popular lossy image compression formats is used by various advanced digital cameras and image editor and processing software tools. Earlier work identified traces of the image JPEG compression history or JPEG anti-forensic processing with reasonable loss of image quality. This aims at removing from a given image the footprints in both the spatial and frequency domain left by JPEG compression. However, efficient forensic Undetectability not obtained. To deal with this problem the present work proposes different forgery detection algorithm such as Ststic image Format Analysis algorithm, lossy compression technique Effect and Place/Transfer Forgery. The result of this algorithm is combined by using Dempster-Shafer combiner which is based on the Dempster-Shafer theory as a framework within which the results of different tools are considered and taken decision. Experimental result of proposed system efficiently detects the Undetectability forgeries when and provides better result when compare with earlier methods.